(untitled) (European Journal of Economics, Finance and Business Development, 2026)
This article examines the role and effectiveness of the corporate governance system in shaping a company’s financial strategy. The study analyzes corporate governance mechanisms, the involvement of the Chief Financial Officer (CFO) in strategic and operational decision-making, financial risk management, and resource utilization. The research demonstrates that an effective corporate governance system contributes to enhanced financial stability, the rational allocation of resources, and increased market competitiveness.